Analisis Bentuk Partisipasi Masyarakat dalam Pengelolaan Badan Usaha Milik Desa di Desa Kanie Kecamatan Maritengngae Kabupaten Sidenreng Rappang - andi alief Darmawansyah; Rais Rahmat Razak; Abdul Abdul (STISIPOL Raja Haji, 2025)
This study aims to analyze the forms of community participation in managing Village-Owned Enterprises (BUMDes) in Kanie Village, Maritenggae District, Sidenreng Rappang Regency. The main problem concerns the low level of community involvement across various stages of BUMDes governance, including planning, implementation, utilization, and evaluation. A qualitative descriptive method was used, with data collected through observation, semi-structured interviews, and documentation. Data analysis employed NVivo 12 Plus to uncover participation patterns and dominant governance principles. The findings indicate that most community participation occurs during the implementation stage, while decision-making and evaluation are dominated by village officials. Low public literacy, limited outreach, and elite domination hinder substantive participation. These results underscore the importance of enhancing transparency, active involvement, and strengthening participatory and accountable governance principles for sustainable BUMDes management.